2011
DOI: 10.1002/pon.1723
|View full text |Cite
|
Sign up to set email alerts
|

The desire for shared decision making among patients with solid and hematological cancer

Abstract: The results show differences between patients with hematological cancer and patients with solid tumors, and these differences concern the preference to participate in medical decisions. Hemato-oncological patients desire less active participation and prefer a more dominant role of the physician in the various areas requiring decisions. Physicians should respect this in the course of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 29 publications
5
49
1
1
Order By: Relevance
“…With regards to age, we were able to replicate the association found by several other studies that younger patients have a stronger desire to decide alone than older patients [23–25, 28, 30, 32]. In the multivariate analyses, we found that older patients were less likely than younger patients to choose an autonomous role over a shared role.…”
Section: Discussionsupporting
confidence: 83%
“…With regards to age, we were able to replicate the association found by several other studies that younger patients have a stronger desire to decide alone than older patients [23–25, 28, 30, 32]. In the multivariate analyses, we found that older patients were less likely than younger patients to choose an autonomous role over a shared role.…”
Section: Discussionsupporting
confidence: 83%
“…One study in patients with haemato-oncological illnesses [17] reported no association between gender and congruence between preferred and perceived participation.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to decision-making, 51% preferred to leave this to staff. There is evidence suggesting that haematological patients wish to take less active participatory role (63% passive role) in the decision-making process than those suffering from solid cancer (29.7% passive role) [10] , furthermore that patients with chronic heart failure has a relatively high wish of being passive (47.8%) [11] . These studies are indicating that the type of illness may influence on the participatory role.…”
Section: Discussion Of Resultsmentioning
confidence: 99%